2020
DOI: 10.21037/atm-20-3986
|View full text |Cite
|
Sign up to set email alerts
|

Which is the optimal management for locally advanced gastric cancer patients with TRG 0 and 1 after R0 resection?

Abstract: Background: Neoadjuvant chemotherapy (NAC) followed by surgery currently offers promise as a strategy for patients with locally advanced gastric cancer (GC). However, there is limited evidence to guide treatment for TRG 0 and 1 patients with locally advanced GC after R0 resection. This study set out to explore the optimal management for TRG 0 and 1 patients with locally advanced GC after R0 resection. Methods:The retrospective data of 154 TRG 0 and 1 patients with locally advanced GC following R0 resection who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The aforementioned methods evaluate patients' response to NAC based on the extent of residual tumor in postoperative tissue specimens, providing clinicians with crucial information regarding patients' treatment response and guiding further treatment strategies. Previous studies have found that for TRG 0 or 1 patients without adverse prognostic factors, the option of no postoperative chemotherapy may be considered, whereas for patients with TRG 2 or 3, postoperative chemotherapy may be necessary [9,10]. However, these methods rely on pathologic results obtained after tumor surgical resection, making them challenging to apply for predictions before NAC.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned methods evaluate patients' response to NAC based on the extent of residual tumor in postoperative tissue specimens, providing clinicians with crucial information regarding patients' treatment response and guiding further treatment strategies. Previous studies have found that for TRG 0 or 1 patients without adverse prognostic factors, the option of no postoperative chemotherapy may be considered, whereas for patients with TRG 2 or 3, postoperative chemotherapy may be necessary [9,10]. However, these methods rely on pathologic results obtained after tumor surgical resection, making them challenging to apply for predictions before NAC.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of typical symptoms in early GC, nearly two-thirds of the patients were diagnosed with extensive local lymph node involvement and/or invasion of adjacent structures in late stages of the disease, the 5-year survival rate is unsatisfactory (Feng et al 2020;Ma et al 2020). Some phase III studies have shown a survival bene t from irinotecan or docetaxel as second-line chemotherapy compared to best supportive therapy (Ford et al 2014; Kang et al 2012;Thuss-Patience et al 2011).…”
Section: Introductionmentioning
confidence: 99%